Geographic Variation in Initiation of Evidence-based Psychotherapy Among Veterans With PTSD. Issue 9 (28th August 2021) - Dufort, Vincent M; Bernardy, Nancy; Maguen, Shira; Hoyt, Jessica E; Litt, Eric R; Patterson, Olga V; Leonard, Christine E; Shiner, Brian
Abstract: Introduction: The United States Department of Veterans Affairs (VA) has invested in implementation of evidence-based psychotherapy (EBP) for post-traumatic stress disorder (PTSD) for over a decade, resulting in slow but steady uptake of these treatments nationally. However, no prior research has investigated the geographic variation in initiation of EBP. Our objectives were to determine whether there is geographic variation in the initiation of EBP for PTSD in the VA and to identify patient and clinic factors associated with EBP initiation. Materials and Methods: We identified VA patients with PTSD who had not received EBP as of January 2016 ( N  = 946, 667) using retrospective electronic medical records data and determined whether they initiated EBP by December 2017. We illustrated geographic variation in EBP initiation using national and regional maps. Using multivariate logistic regression, we determined patient, regional, and nearest VA facility predictors of initiating treatment. This study was approved by the Veterans Institutional Review Board of Northern New England. Results: Nationally, 4.8% ( n  = 45, 895) initiated EBP from 2016 to 2017, and there was geographic variation, ranging from none to almost 30% at the 3-digit ZIP code level. The strongest patient predictors of EBP initiation were the negative predictor of being older than 65 years (OR = 0.47; 95% CI, 0.45-0.49) and the positive predictor of reporting military-related sexual trauma (OR = 1.96; 95% CI, 1.90-2.03). The strongest regional predictors of EBP initiation were the negative predictor of living in the Northeast (OR = 0.89; 95% CI, 0.86-0.92) and the positive predictor of living in the Midwest (OR = 1.47; 95% CI, 1.44-1.51). The only nearest VA facility predictor of EBP initiation was the positive predictor of whether the facility was a VA Medical Center with a specialized PTSD clinic (OR = 1.23; 95% CI, 1.20-1.26). Conclusion: Although less than 5% of VA patients with PTSD initiated EBP, there was regional variation. Patient factors, region of residence, and nearest VA facility characteristics were all associated with whether patients initiated EBP. Strengths of this study include the use of national longitudinal data, while weaknesses include the potential for misclassification of PTSD diagnoses as well as the potential for misidentification of EBP. Our work indicates geographic areas where access to EBP for PTSD may be poor and can help target work improving access. Future studies should also assess completion of EBP for PTSD and related symptomatic and functional outcomes across geographic areas.